Detection of Antibody against Fungal Glucosylceramide in Immunocompromised Patients: A Potential New Diagnostic Approach for Cryptococcosis - Qureshi, Asfia; Wray, Dannah; Rhome, Ryan; Barry, William; Del Poeta, Maurizio (Mycopathologia (1975), 2012)
We have developed an ELISA to determine the value of anti-glucosylceramide antibody for the prediction of disseminated cryptococcosis in immunocompromised subjects and performed a clinical prospective study at the Medical University of South Carolina. The study enrolled a total of 53 patients who were free of active fungal diseases at the time of enrollment but at risk of developing one because they were all immunocompromised, e.g ., (1) patients positive for HIV and (2) patients post- or awaiting solid organ transplantation. Among 53 patients enrolled, two patients developed invasive cryptococcosis, and in both patients, IgM anti-GlcCer was detected in sera using the ELISA at least 6 weeks prior to the clinical presentation of the brain disease. These results were corroborated by a cryptococcal antigen lateral flow assay, which was also positive in serum prior to the development of meningoencephalitis. However, a high number of positive results were also detected in patients with no evidence of cryptococcosis. This study highlights the potential utility of this new assay in early diagnostic testing algorithms for patients at risk for cryptococcosis, but further investigations are needed to validate the sensitivity and specificity of the glucosylceramide ELISA as a predictor of cryptococcosis.